Visual Culture, Religion, and Politics in the Modern Iranian Public Sphere: The resemiotization of Twelver Shiite Culture in the Mobilization of Protest - Ingvild Flaskerud (Tidsskrift for Islamforskning)
To contest the results of the Iranian presidential election in 2009, mobilize street protest, and document the regime’s responses protesters disseminated posters, photographs, and films on social media platforms. In this article I discuss how their use of signs associated with Twelver Shiite visual, material and performative culture were used to mobilize opposition against authorities who claim to be acting as guardians of a society based on the creed. By giving attention to signs’ coexisting discursive contexts and modality, the study seeks to advance the conceptualization of ‘recontextualization’ and ‘resemiotization’ in the semiotic study of cultural codes, and to connect the study of Twelver Shiite visual, material and performative culture to the sphere of public discourse in modern Iran.